O Sponad Juliana Przybosia i Władysława Strzemińskiego - Anna Jaworska (Przestrzenie Teorii)
Julian Przyboś's poetic volume Sponad [From Above] with artwork by Władysław Strzemiński is not a rewarding material for an interpretation since due to the tight coupling of the two remarkably powerful artistic personalities and the two kinds of sensitivity - literary and that of an artist, an analysis of poetic works in the shape given to them by an artist must be tainted with the latter's views and must contain in itself interpretational doubleness. Thanks to graphic layouts and illustrations made by Strzemiński, the space of the poems became palpable and visible. Thus, not only individual words were extracted and emphasised, but also the "inter-words" somewhere between them, stating what was only implied or unstated. Strzemiński's layouts conceal in themselves a set fuse for a bomb which poetry, exploding with new layers of meaning, may become.